TIGvival: High-resolution spectroscopic monitoring of LPV stars. Issue Volume 14:Issue S343(2019) (August 2018) - Wolter, Uwe; Engels, Dieter; Aringer, Bernhard; Freytag, Bernd
Abstract: TIG vival is a spectroscopic monitoring program of long-period variables (LPV) using our robotic telescope TIGRE. Since 2013, we obtain low-noise, high-resolution spectra (R= 20 000) that cover the optical regime (3800 Å to 8800 Å). We are now continuously monitoring 7 LPVs with different periods and chemical properties. Our 350+ spectra evenly sample the target cycles, as far as ground-based observations allow. Analyzing the TIG vival spectra of Mira as a sample case, our measurements indicate that the strength of the TiO-absorption is phase-shifted with respect to the visual light curve.